Perilaku Konsumen di Kafe - Alisa Rahadiasmurti Isfandiari; Marheni Eka Saputri (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
The increasingly fierce business competition conditions and increasing creativity in Bandung require business people, especially in the culinary field, to innovate. One Eighty Coffee and Music is one cafÃ© that innovates by having a unique concept. However, besides the unique things, there are other factors that encourage consumer behavior in making purchasing decisions at a cafÃ©. Therefore, the purpose of this study was to find out the most dominant and significant factors in encourage purchasing decisions in One Eighty Coffee and Music. This research is a descriptive type research, using quantitative research methods. The measurement scale in this study is a Likert scale. The population in this study is, One Eighty Coffee and Music consumers with a sample of 100 respondents. The sampling technique used is non-probability sampling with one type of grouping namely accidental sampling. The process of data collection is to use primary data and secondary data. The data analysis technique used is factor analysis using SPSS 23 for processing the data. In this study, there are 4 new components that encourage consumers to make purchases at One Eighty Coffee and Music. The four components that can cover all these factors are hedonist, availability and supply, promotion and advertising, and health benefits. Based on the calculation of loading factors, the health benefit factor is the most dominant and significant factor in encourage purchasing decisions in One Eighty Coffee and Music, meaning consumers make purchases at One Eighty Coffee and Music because consumers are aware of their health and One Eighty Coffee and Music is trusted have a healthy menu that can fulfill consumer desires in maintaining personal health and the desire to consume healthy products. Therefore, One Eighty Coffee and Music is expected to provide food that can fulfill health, not just filling, but also makes consumers healthy. Keywords: Consumer behavior, Factor Analysis, Purchasing Decisions